Risk Management in Wealth Protection from an Islamic Economic Perspective - Aini, Ihdi; Sugianto, Sugianto; Marliyah, Marliyah (PT. Riset Press International, 2025)
This study aims to explore risk management in wealth protection from the perspective of Islamic economics. The main issue is how Islamic economics provides sustainable risk management solutions that align with Sharia principles for safeguarding individual and collective wealth. The scope of this research includes relevant Islamic economic concepts, mechanisms, and instruments for wealth protection, such as zakat, waqf, and takaful. The research method used is qualitative descriptive with a library research approach, where data is collected from various sources such as scientific journals, books, and reports related to Islamic economics and risk management. The data analyzed included Islamic economic theories from experts such as Al-Ghazali and Ibn Khaldun and contemporary concepts related to Sharia risk management. The results show that risk management in Islamic economics aims not only to protect wealth but also to ensure social balance and the distribution of economic justice. An interesting finding from this study is the application of instruments such as zakat and waqf that can effectively reduce people's financial risks, help redistribute wealth, and create economic resilience. In addition, the concept of takaful as Sharia-based insurance also plays a role in mitigating individual financial risks fairly and transparently. The implications of this study reinforce the importance of integrating Sharia principles into economic policy to achieve long-term financial sustainability and stability.